PENERAPAN KOOPERATIF TIPE TRADE A PROBLEM PADA MATERI BARISAN DAN DERET KELAS XI SMA - Melisa Andini Erno; Dede Suratman; Edy Yusmin (Universitas Tanjungpura, 2019)
AbstractThis research aimed to determine the effectiveness of the implementation of Trade A Problem type as learning model in teaching arithmetic sequence and series in the Class XI students of “SMAN 01 Meliau”. The research method used was pre-experimental method with one-shot case study design. The aspect to determine the effectiveness of this research are class management, students activity and student’s outcomes. The tools of data collecting were 4 iteams essays, teacher’s class management and students’ activities observational sheets. Through descriptive analysis, founded that the result of teachers’ class management was categorized as good (3,37), while the students’ activities result categorized as active (76,25%) and student’s completeness not fulfilled classically (only 21 students or 65,6% of students can fulfill the standard completeness). Trade A Problem type as learning model in teaching arithmetic sequence and series in the class XI students of “SMAN 01 Meliau” is effective on the aspects of class management and students activity. Keywords: Arithmetic Sequence and Series, Effectiveness, Trade a problem type Of Cooperative Model